Extracellular Vesicles: How Drug and Pathology Interfere With Their Biogenesis and Function - Cesselli, Daniela; Parisse, Pietro; Aleksova, Aneta; Veneziano, Claudia; Cervellin, Celeste; Zanello, Andrea; Beltrami, Antonio Paolo (Frontiers in Physiology, 2018)
Extracellular vesicles (EV) are at the center of an intense activity of investigation, both for their possible employment as biomarkers of ongoing pathologic processes and for their broad range of biological activities. EV can promote tissue repair in very different pathologic settings, including hindlimb and myocardial ischemia. Importantly, the exact mode of action of EV is still partly understood, since they may act by modulating growth factors and cytokines, signaling pathways, and by transferring non-coding RNAs to target cells. However, the term EV identifies cell derived, enveloped particles very heterogeneous in size, composition, and biogenesis. Therefore, part of the controversies on the biological effects exerted by EV are a consequence of differences in methods of separation that result in the enrichment of different entities. Since technical challenges still hamper the highly specific sorting of different EV subpopulations, up to now only few investigators have tried to verify differences in the biological effects of specific EV subtypes. This review summarizes the current state of the art on the comprehension of mechanisms involved in EV biogenesis and release, which is a prerequisite for understanding and investigating the impact that pathology and drug therapy may exert on the secretion and composition of EV. Finally, we described both the mechanism involved in the modulation of EV secretion by drugs commonly used in patients affected by heart failure, and how pathophysiological mechanisms involved in heart disease modify EV secretion.